Suppression of the SUGAR‐DEPENDENT1 triacylglycerol lipase family during seed development enhances oil yield in oilseed rape (Brassica napus L.). Issue 3 (21st November 2012) - Kelly, Amélie A.; Shaw, Eve; Powers, Stephen J.; Kurup, Smita; Eastmond, Peter J.
Summary Increasing the productivity of oilseed crops is an important challenge for plant breeders and biotechnologists. To date, attempts to increase oil production in seeds via metabolic pathway engineering have focused on boosting synthetic capacity. However, in the tissues of many organisms, it is well established that oil levels are determined by both anabolism and catabolism. Indeed, the oil content of rapeseed (Brassica napus L.) has been reported to decline by approximately 10% in the final stage of development, as the seeds desiccate. Here, we show that RNAi suppression of the SUGAR‐DEPENDENT1 triacylglycerol lipase gene family during seed development results in up to an 8% gain in oil yield on either a seed, plant or unit area basis in the greenhouse, with very little adverse impact on seed vigour. Suppression of lipolysis could therefore constitute a new method for enhancing oil yield in oilseed crops.